The Correlation of Depression Level with Tumor Necrosis FactorAlpha (TNF-α) Concentration in Uncontrolled Bronchial AsthmaPatients - Apriansyah, Muhammad Ali; Putranto, Rudi; Salim, Eddy Mart; Shatri, Hamzah (Jurnal Penyakit Dalam Indonesia, 2016)
Introduction. Depression occurs at high rates in people with chronic diseases, including bronchial asthma, with the prevalence of depression approaches 50% in tertiary care asthma clinic. Tumor necrosis factor alpha (TNF-α) is known to play a critical role in the pathogenic mechanism of a number of chronic inflammatory disease, including bronchial asthma and depression. There has not been any research data on the subject in Indonesia. The objective of this study was to investigate the correlation between depressive level and TNF-α level in uncontrolled bronchial asthma. Methods. This was a cross sectional study conducted in 40 patients with uncontrolled bronchial asthma at the allergy immunology clinic outpatient of Dr Moh Hoesin Hospital Palembang, during June 2014 until August 2014. Uncontrolled bronchial asthma was assessed using the Asthma Control Test (ACT) questionnaire, whereas depressive symptoms were assessed by Beck Depression Inventory (BDI) questionnaire, and diagnosis was confirmed by the criteria of the Diagnostic and Statistical Manual for Psychiatry-IV Text Revision (DSM-IV TR) / International Code Diagnose 10 (ICD-10). Serum levels of TNF-α was measured by the method of quantitative enzyme-linked immunosorbent assay (ELISA). Results. The median value of the level of depression and serum TNF- α in this study were 16 (10 - 45) and 4.09 (1.29 - 19.57) pg/mL. There was no significant correlation between depressive level and TNF-α level ( r = -0.265 , p = 0.098 ). Conclusions. There was no significant correlation between depressive level and TNF-α level in uncontrolled bronchial asthma